Análise da agenda do financiamento do SUS: diferentes contextos, mesmas escolhas? - Magdalena, Patricia Cristina (2012)
The present study focus on the budgetary theme of the Unified Health System (SUS, Sistema Único de Saúde) financing, in order to make a historical reconstruction to offer evidence about the collision between healthcare and economic areas and trying to understand which factors reflected on the difficulty of resolving the issue throughout the period following its approval in the 1988 Federal Constitution.. Thus, we sought to understand which discomfitures and restrictions were imposed to such policy, especially under the Fernando Henrique Cardoso and Lula administrations. We sought to comprehend to what extent the different social, political and economic contexts of those administrations led to the decision of not prioritizing an understanding of the lack of available resources. In this sense, we aimed at verifying whether there can be a continuity line between those two administrations. We highlight all the difficulties of financial nature such universal policy had to face from the 1990’s to 2010, the struggle for increased investment and the solutions proposed, particularly the CPMF tax (Provisional Contribution Over The Transit Or Transmission of Values and Credit and Rights of Financial Nature) and the Constitutional Amendment N. 29 as well as its regulations. Further we highlight the role of the Executive and Legislative in the making of healthcare legislation as well as the conflicts between the Ministries of Health and Finance, and the role of inspection and control offices (The Union Budgetary Court and the Federal Public Ministry). In our results, we present evidence that there has been a continuity in the approach to the subject of SUS financing by both the FHC and Lula administrations and that the prevailing agenda was that of an economic standpoint. In spite of that, the healthcare area managed to keep itself afloat as a social, universal right and obtained several advancements.